Engineering in chalk : proceedings of the Chalk 2018 Conference, Imperial College, London on 17 and 18 September 2018 - Lawrence, J. A.; Preene, M.; Lawrence, Ursula; Buckley, R. (ICE Publishing, 2018)
This volume contains the proceedings of a major two-day international conference on Engineering in Chalk, organised by the British Geotechnical Association (BGA), with support from the Engineering Group of the Geological Society (EGGS). Bringing together the knowledge and experience gained in the last three decades the papers in this collection present research and case histories to provide a definitive up to date perspective on a wide range of technical themes relating to Engineering in Chalk.